El arte rupestre de la cuenca del río Coclé del Sur, Panamá - Mayo, Carlos; Mayo, Julia (Revista Española de Antropología Americana, 2007)
One of the goals of the «Proyecto Arqueológico Coclé» is the study of rock art in the Coclé Sur Basin. Our purpose is to inventory petroglyphs emphasizing subject matter, and stylistic and technological attributes, with a view to comparing their imagery with that of Gran Coclé polychrome pottery and thus determine whether we can identify a stylistic/technology sequence through time. We have made a map of recorded petroglyphs and their designs, created with G.I.S. This procedure has enabled us to identify relationships between the petroglyphs motifs and designs and their geographic and topographic location.